2008
DOI: 10.1210/en.2007-1516
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Janus Kinase-2 Dependent Leptin Signaling in Natural Killer (NK) Cells: A Novel Mechanism of NK Cell Dysfunction in Diet-Induced Obesity

Abstract: Leptin acts not only as an anorexigenic hormone but also regulates cell-mediated immunity via leptin receptors (Ob-R) expressed on T and B lymphocytes. However, the impact of leptin on natural killer (NK) cells is currently elusive. We evaluated leptin effects on NK cells in relation to the body weight in rats using in vivo and in vitro approaches. Leptin was injected iv in male lean and diet-induced obese Lewis and F344 rats. NK cell numbers were analyzed in blood and spleen by fluorescence activated cell sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
3
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 42 publications
8
70
3
4
Order By: Relevance
“…[25][26][27] It has also been reported that the proinflammatory state of obesity may induce an attenuated response of immune competent cells to an acute endogenous or exogenous leptin challenge and inhibit the promigratory and activating effects of a leptin challenge on NK cells. 28 These reports along with the results of the present study support the hypothesis that obesity may lead to impaired immune functions and that low leptin levels among RCC patients suggest reduction or loss of leptin's anti-tumour effect (Figure 1). This study has several strengths including the exclusion of renal cancer cases with different underlying pathophysiology and the blinded evaluation in one batch of the serum analytes.…”
Section: Discussionsupporting
confidence: 88%
“…[25][26][27] It has also been reported that the proinflammatory state of obesity may induce an attenuated response of immune competent cells to an acute endogenous or exogenous leptin challenge and inhibit the promigratory and activating effects of a leptin challenge on NK cells. 28 These reports along with the results of the present study support the hypothesis that obesity may lead to impaired immune functions and that low leptin levels among RCC patients suggest reduction or loss of leptin's anti-tumour effect (Figure 1). This study has several strengths including the exclusion of renal cancer cases with different underlying pathophysiology and the blinded evaluation in one batch of the serum analytes.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, the same positive effect was found for infection with pneumococcal pneumonia [21]. Comparing diet-induced obese (dio) with lean animals, Mito et al [22] showed a different cytokine response toward a leptin treatment in lean and dio mice and Nave et al [23] demonstrated a lack of intracellular signaling events in NK cells after leptin treatment in dio rats. Recent data additionally revealed a very distinct migratory performance, especially of B-and T-lymphocytes, in dio mice challenged by different chemokines [24].…”
Section: Introductionmentioning
confidence: 82%
“…Both proteins work as negative regulators of leptin-induced activation of the JAK/STAT pathway (Morris & Rui 2009). In addition to central leptin resistance, several studies on obesity models have observed attenuated leptin signaling in peripheral tissues (Prpic et al 2003, Lam et al 2006, Steinberg et al 2006, Nave et al 2008. In most cases, an increase in PTP1B or SOCS3 levels was associated with this attenuated response to leptin.…”
Section: Leptin Resistancementioning
confidence: 99%